Decomposition of potent greenhouse gas sulfur hexafluoride (SF6) by kirschsteinite-dominant stainless steel slag - Zhang, J.; Zhou, J.; Xu, Z.; Li, Y.; Cao, T.; Zhao, J.; Ruan, X.; Liu, Jian; Qian, G. (American Chemical Society, 2014)
In this investigation, kirschsteinite-dominant stainless steel slag (SSS) has been found to decompose sulfur hexafluoride (SF6) with the activity higher than pure metal oxides, such as Fe2O3and CaO. SSS is mainly made up of CaO·FeO·SiO2(CFS)/ MgO·FeO·MnO(RO) phase conglomeration. The SF6decomposition reaction with SSS at 500-700 C generated solid MF2/MF3and gaseous SiF4, SO2/SO3as well as HF. When 10 wt % of SSS was replaced by Fe2O3or CaO, the SF6decomposition amount decreased from 21.0 to 15.2 or 15.0 mg/g at 600 C. The advantage of SSS over Fe2O3or CaO in the SF6decomposition is related to its own special microstructure and composition. The dispersion of each oxide component in SSS reduces the sintering of freshly formed MF2/MF3, which is severe in the case of pure metal oxides and inhibits the continuous reaction of inner components. Moreover, SiO2in SSS reacts with SF6and evolves as gaseous SiF4, which leaves SSS with voids and consequently exposes inner oxides for further reactions. In addition, we have found that oxygen significantly inhibited the SF6decomposition with SSS while H2O did not, which could be explained in terms of reaction pathways. This research thus demonstrates that waste material SSS could be potentially an effective removal reagent of greenhouse gas SF6. © 2013 American Chemical Society.